Methodology for the collaboration in supply chains with a focus on continuous improvement (2016)
A collaborative relationship between companies in a supply chain makes it possible to improve both the performance and the results of the companies and of the supply chain. Several studies have analyzed supply chains, but few studies have proposed the application of tools for continuous improvement in a collaborative manner within the supply chain. The objective of this work is to present a methodology for the collaboration in a supply chain with a focus on continuous improvement. Three case studies were conducted with Brazilian multinational focal companies that manufacture technology-based products. It was seen that relationships, trust, the exchange of information, and the sharing of gains and risks sustains collaborative practices focused on continuous improvement. The proposed methodology considers the need for supplier development, for the monitoring of the supplies, and for the development of a partnership for problem solving through the application of tools for continuous improvement.